CRYSTAL-BASED LEARNING AND SELF-REGULATION: PROCESS AND EXPECTED RESULTS - Thummakul, Doungnetre; Gawglaun, Pimkhun (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
Crystal-based learning and self-regulation are teaching guidelines that help learners achieve desired learning behavior with the following five basic processes: critical thinking, generating new knowledge, value assessment, integration and communication. These principles promote learners in gradual internal behavior modification aimed at controlling external behaviors, which will result in creative learning with improved learning outcomes. In addition, instructors will be external factors with direct influence on learners. If these instructors can arrange the appropriate learning environments, motivating and being able to create learners who can regulate emotions that affect their learning, this will help to create work responsibility planning, and having learning goals leading to intellectual growth. These are issues instructors can promote self-directed and development in the acquisition of knowledge for learners to create intellectual processes and while crystal-based learning. Thus, it can result in learning and achieving good academic outcomes in the future.